1994
DOI: 10.1093/clinids/18.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pentoxifylline Therapy for Patients with AIDS-Related Wasting: Pilot Study

Abstract: Severe weight loss is a common manifestation of advanced infection with the human immunodeficiency virus. The level of tumor necrosis factor alpha (TNF-alpha), an inducer of cachexia in laboratory animals, is elevated in the serum of some patients with AIDS. In a pilot study, five patients with unexplained AIDS-related wasting were treated with pentoxifylline, a known suppressor of TNF-alpha production. Three of the five patients had elevated baseline serum levels of TNF-alpha, and these three patients did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Until the mechanism by which thalidomide causes weight gain and the clinical significance of the increases in virus load and TNFa are understood, it is difficult to define a specific role for thalidomide in the treatment of HIV-associated wasting. A variety of other weak cytokine suppressors, including pentoxifylline [97], N-3 fatty acids [98], and ketotifen [76,99] have been studied in subjects with HIV-associated weight loss, but their use for this indication is not supported by current data.…”
Section: Cytokine Suppressionmentioning
confidence: 99%
“…Until the mechanism by which thalidomide causes weight gain and the clinical significance of the increases in virus load and TNFa are understood, it is difficult to define a specific role for thalidomide in the treatment of HIV-associated wasting. A variety of other weak cytokine suppressors, including pentoxifylline [97], N-3 fatty acids [98], and ketotifen [76,99] have been studied in subjects with HIV-associated weight loss, but their use for this indication is not supported by current data.…”
Section: Cytokine Suppressionmentioning
confidence: 99%
“…A number of agents like anabolic steroids (oxandrolone, nandrolone), megesrtol acetate, thalidomide, human chorionic gonadotropin, pentoxyfiline, amino acid mixtures and omega 3 fatty acids have been tried in this setting with variable efficacy but potential side effects. [8690] Only testosterone administration has proved useful to increase lean body mass, especially in conjunction with progressive resistance training. Supraphysiologic dose GH administration is currently reserved for severe wasting refractory to other treatments.…”
Section: Aids Wasting Syndromementioning
confidence: 99%
“…In a small pilot study in HIV-infected patients, pentoxifylline provided no evidence of weight gain after 6 weeks of treatment. 250 Another group of investigators found that in decreasing TNF-␣ secretion, pentoxifylline increased the mycobacterial load in macrophages from AIDS patients resulting in disseminated Mycobacterium avium-intracellulare complex infection. 251…”
Section: Pentoxifyllinementioning
confidence: 99%